Pengaruh Penambahan Patikel dan Ukuran Partikel Limbah Batang Kelapa Sawit Sebagai Subtitusi Pasir Terhadap Kualitas Paving Block - Lusi H Manalu; Irawaty Irawaty; Tito Sucipto (Program studi Kehutanan USU, 2013)
The wastes of palm’s trunk will be increasingly along with the extensive of palm’s plantation in Indonesia. It is a lignocelluloses material that can be used as raw materials for the manufacture of paving block, although the exact composition and size to produce good paving block unknown. Therefore, there is a research by using the variation of composition of paving block 1:2:3:0.5, also the addition of the palm oil’s trunk is substituted with sand as the mixture of paving block with 2.5% and 5% as the composition and the particle size is 20 also 40 mesh. The objectives of this research are to evaluate the characteristic and the influence of the addition the trunk of palm oil to the paving block quality. The results of testing the mechanical and physical properties of paving block with treatment levels of particle and particle size based on SNI 03-0691-1996. The results are from 14.89 to 29.14 MPa is the quality of B-C. The results of testing the physical properties, water absorption 0.42%-1.51%,i.e. The quality of A, 9.2% -11.89% porosity, resistance to sodium sulfate does not fill the standard with decreasing weight from 0.57 to 1.89% . Almost all of the characteristics of the paving block treatments comply SNI 03-0691-1996. Keywords: cement, oil palm, paving blocks, mechanical and physical properties.